INVESTIGATING IMPULSIVE BUYING IN THE DIGITAL ERA: THE IMPACT OF LIFESTYLE AND E-WALLET USAGE ON GENERATION Z - Yulfiswandi; Slevia; Candy (Jurnal Studia Akuntansi dan Bisnis (The Indonesian Journal of Management & Accounting), 2026)
This research seeks to explore how lifestyle choices and the use of e-wallets affect impulsive buying in Generation Z located in Batam City, including how self-control acts as a moderating factor. The research used a quantitative approach involving 264 respondents selected through convenience sampling. Data were collected through online questionnaires and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The results indicate that lifestyle and e-wallet usage positively affectimpulsive buying. However, self-control was not able to moderate the relationship between lifestyle and e-wallet usage on impulsive buying. In addition, the research model was able to explain 70.6% of the variation in impulsive buying. Overall, impulsive buying among Generation Z is influenced by lifestyle factors, technological convenience, and an individual’s ability to exercise self-control.